2017
DOI: 10.1007/s10640-017-0159-y
|View full text |Cite
|
Sign up to set email alerts
|

Does FDI Bring Environmental Knowledge Spillovers to Developing Countries? The Role of the Local Industrial Structure

Abstract: This paper examines the environmental knowledge externalities of FDI within and across cities in an emerging economy context. It argues that the extent of these environmental externalities is contingent upon local industrial agglomeration. Using a panel dataset of 280 Chinese prefectural cities from 2003 to 2012, we employ a spatial economic approach. Although limited to evidence from soot and SO 2 pollutants, our results suggest that FDI brings overall positive environmental knowledge externalities to a regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 92 publications
0
36
0
Order By: Relevance
“…PSPE , PPTC , and SEE indicate the intensity of air pollution control policies, the public environmental participation, and the media environmental monitoring, respectively. is a collection of the control variables mainly expressed from STIRPAT model, including economic development [ 31 ], industrial structure [ 5 ], S&T expenditure [ 32 ], energy consumption [ 33 ], population density [ 31 ], and the degree of opening-up reflected by foreign direct investment (FDI) [ 34 ]. The details of the variables can be seen from Section 4 below.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…PSPE , PPTC , and SEE indicate the intensity of air pollution control policies, the public environmental participation, and the media environmental monitoring, respectively. is a collection of the control variables mainly expressed from STIRPAT model, including economic development [ 31 ], industrial structure [ 5 ], S&T expenditure [ 32 ], energy consumption [ 33 ], population density [ 31 ], and the degree of opening-up reflected by foreign direct investment (FDI) [ 34 ]. The details of the variables can be seen from Section 4 below.…”
Section: Methodsmentioning
confidence: 99%
“…The spatial relationship is a known phenomenon in ecological research and refers to the relationship between certain variables observed in different regions [ 5 ]. As environmental pollution has spatial spillover effects, air pollution in one region is not independent of other regions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with MAR's externalities, many studies have confirmed that industry specialisation is more beneficial to innovation intensity (INA) than industry diversity [31][32][33]35,49,50], which is especially true for technology-intensive manufacturing [39,41,51]. MAR externalities argue that the geographical proximity of similar industries dramatically facilitates the sharing of infrastructure, intermediate inputs, and the labour market, subsequently fostering knowledge spillover.…”
Section: Theoretical Modelmentioning
confidence: 93%